Assessing the Complex Operation of Blended Learning for English Instruction in a Public High School in the Philippines - Danica Jae B. Sagun; Greg T. Pawilen; Sarah Jen C. Paccarangan; Rufo Gil Z. Albor; Hannah L. Patindol; Phrygian P. Almeda; Daisy V. Pelegrina (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: The study aims to describe stakeholders' experiences in blended learning at a public high school in Laguna, Philippines, during the COVID-19 pandemic. Method: This qualitative study was conducted through Focus Group Discussions (FGD) with English teachers, learners, and the Information and Communications Technology (ICT) coordinators and a Key Informant Interview (KII) with the English department head. Results: Three main themes emerged from the study: factors that encourage stakeholder collaboration, barriers to stakeholder collaboration, and solutions to collaboration challenges. Novelty: Overall, the study results show how important collaboration is in overcoming the difficulties associated with blended learning and creating a positive learning environment for the stakeholders. By fostering a collaborative environment, stakeholders can work together to address the complexities of blended learning, optimize the benefits of the modality, and create a compelling and engaging learning experience for all learners.